Analisis Putusan Sela Pengadilan Negeri Padang Kelas 1A Tentang Kompetensi Absolut Pengadilan Niaga (Putusan Sela : 54/Pdt.G/2024/PN Pdg) - Yunimar Yunimar; Dwikornida Dwikornida; Yudha Mardinata (Normative Jurnal Ilmiah Hukum, 2026)
A valid agreement based on Article 1320 of the Civil Code requires agreement, competence, a specific object, and a lawful cause, binding the debtor to fulfill the performance with the general guarantee of Articles 1131-1132 of the Civil Code. If one party does not fulfill its performance, it is called a breach of contract. The settlement of the breach of contract can be done in court and out of court. Settlement in court, the judge sees whether the dispute is within his authority in terms of relative competence or absolute competence in adjudicating. Disputes that occur by business actors, the authority of the commercial court is to resolve them. A dispute resolved in the commercial court may not be sued back to the district court. In this regard, the Interim Decision Number 54/Pdt.G/2024/Pn Pdg of the district court, the Padang district court has decided that it is not within its authority to resolve the dispute. The formulation in this research is How is the consideration of the judge of the Padang District Court Class 1A Padang in the interim decision regarding the Absolute Competition of the Commercial Court (Interim Decision: 54/Pdt.G/2024/Pn Pdg)?, How is the analysis of the Interim Decision of the Padang District Court Class 1A Regarding the Absolute Competition of the Commercial Court (Interim Decision: 54/Pdt.G/2024/ Pn Pdg)? This research uses a descriptive juridical normative legal research method, the data required is secondary data with data collection through literature studies, data processing used in this research uses editing and coding techniques. The results of this study indicate that 1. The judge's consideration in the Interim Decision 54/Pdt.G/2024/PN Pdg which granted the exception of error in persona and absolute competence because the defendant had been bankrupt since March 13, 2024, so that the plaintiff was wrong to sue an individual instead of a curator, the dispute over default of the Sale and Purchase Deed No. 06/2022 entered the realm of the Commercial Court, so that the judge stated that the Padang District Court did not have the authority to handle the dispute of the bankrupt debtor according to Law Number 37 of 2004, 2. legally, the Interim Decision Number 54/Pdt.G/2024/PN Pdg stated that the Padang District Court did not have absolute authority over the dispute over default of the bankrupt debtor, because absolute authority lies with the Commercial Court based on Article 300 paragraph (1) of Law Number 37 of 2004, so that the judge is obliged to consider the main points of the dispute and the petitum as a whole, with resolution being through akkoord or settlement of bankrupt assets by the curator. Therefore, the author suggests that plaintiffs be more discerning in submitting lawsuits to the competent courts with both relative and absolute competence.